Preferential gene retention increases the robustness of cold regulation in Brassicaceae and other plants after polyploidization. (21st February 2020) - Song, Xiao-Ming; Wang, Jin-Peng; Sun, Peng-Chuan; Ma, Xiao; Yang, Qi-Hang; Hu, Jing-Jing; Sun, Sang-Rong; Li, Yu-Xian; Yu, Ji-Gao; Feng, Shu-Yan; Pei, Qiao-Ying; Yu, Tong; et al.
Abstract: Cold stress profoundly affects plant growth and development and is a key factor affecting the geographic distribution and evolution of plants. Plants have evolved adaptive mechanisms to cope with cold stress. Here, through the genomic analysis of Arabidopsis, three Brassica species and 17 other representative species, we found that both cold-related genes ( CRGs ) and their collinearity were preferentially retained after polyploidization followed by genome instability, while genome-wide gene sets exhibited a variety of other expansion mechanisms. The cold-related regulatory network was increased in Brassicaceae genomes, which were recursively affected by polyploidization. By combining our findings regarding the selective retention of CRGs from this ecological genomics study with the available knowledge of cold-induced chromosome doubling, we hypothesize that cold stress may have contributed to the success of polyploid plants through both increasing polyploidization and selectively maintaining CRGs during evolution. This hypothesis requires further biological and ecological exploration to obtain solid supporting evidence, which will potentially contribute to understanding the generation of polyploids and to the field of ecological genomics.